Depression Status, Lifestyle, and Metabolic Factors With Subsequent Risk for Major Cardiovascular Events: The China Cardiometabolic Disease and Cancer Cohort (4C) Study - Chen, Xi; Liu, Zhelong; Yang, Yan; Chen, Gang; Wan, Qin; Qin, Guijun; Yan, Li; Wang, Guixia; Qin, Yingfen; Luo, Zuojie; Tang, Xulei; Huo, Yanan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background We aimed to evaluate the association between depression and major cardiovascular events and test whether the relationship between depression and cardiovascular events is influenced by lifestyle or metabolic risk factors. Methods The China Cardiometabolic Disease and Cancer Cohort (4C) Study was a nationwide, multicenter, prospective cohort study. About 92,869 participants without cardiovascular disease or cancer at baseline were included. Depression status was evaluated by the Patient Health Questionnaire-9 (PHQ-9). Lifestyle information was collected by the questionnaire, and metabolic risk factors including waist circumference, blood pressure, lipid profiles, and plasma glucose were measured. Major cardiovascular events including cardiovascular death, myocardial infarction, stroke, and hospitalized or treated heart failure events were validated based on medical records. Results During an average of 3.8 years of follow-up, we detected 2,076 cardiovascular events and showed that participants with depressive symptoms had an increased risk for cardiovascular events after adjustments [hazard ratio (HR): 1.29; 95% confidence index (CI): 1.08–1.53]. Stratified on metabolic risk status, the relationship between depression and cardiovascular events tended to be stronger according to the increasing numbers of metabolic risk factors, with HR (95% CI) of 0.98 (0.72–1.35) in the category with 0–2 metabolic risk factors, 1.36 (0.996–1.87) and 1.47 (1.13–1.92) for those with 3, and 4–5 metabolic risk factors, respectively, indicating an interaction effect (P = 0.039). Conclusion Depression was independently associated with an increased risk of major cardiovascular events. The effect was particularly prominent among populations at higher metabolic risk.